Use of Social Media Marketing among MSMEs: Driving and Inhibiting Factors - Sulasih sulasih; Weni Novandari; Agus Suroso; Refius Pradipta Setyanto (Jurnal Manajemen Indonesia, 2024)
This study aims to determine the factors driving and inhibiting social media marketing use among Small, Micro, and Medium Enterprises (MSMEs). Data were analyzed using the quantitative descriptive technique as percentages. This study also used confirmatory factor analysis (CFA). Based on the results of the descriptive statistical analysis, it was found that the driving factor for MSMEs in Banyumas to use social media was to engage with consumers. On the contrary, the main factors that hinder the use of social media are the lack of time to create consistent and scheduled content and the difficulty in determining interesting topics. Meanwhile, the CFA analysis revealed that the main driving factor contributing to the highest use of social media use is seen from eigenvalues, that is, that social media is used for marketing activities. The main inhibiting factor seen from the eigenvalues is the limited time to create consistent and scheduled content. In addition to that, difficulty in finding followers, network restrictions, and unsupported features of mobile phones are other factors that inhibit social media use. The originality of this research is considered very limited, as it only examines the driving and inhibiting factors for microscale MSMEs. More research should focus on a widely used social media platform and the type of business because every business has different characteristics. Keywords — MSMEs; Social Media; Technology